Strī vimarśa ke āyāma - Śarmā, Urmilā (Haṃsa Prakāśana, 2022)
Study on the depiction of women and feminism in the works of Mannu Bhandari, 1931-2021, and Kr̥shṇā Sobatī, Hindi authoresses
Includes bibliographical references
Keywords: Bhandari; Mannu; Sobatī; Kr̥shṇa; Women in literature; Feminism in literature